FLEXIBLE COST STRUCTURES TO OVERCOME THE GLOBALIZATION AND COMPETITIVENESS IN THE COMPANIES - Rodríguez Chávez, Agustin (2010)
The present world-wide tendency indicates that the companies to face the exigencies of the global competition originated by the permanent technological innovation and the greater exigency of the client, in quality and the prices of products, are orienting their resource, knowledge and efforts in doing that their processes of businesses, processes productive and organization are flexible to obtain a fast answer to those exigencies. But the costs originated by that answer are forcing the companies to accede to the technological innovation through services of manufacturing, external processes and outsourcing. Nevertheless the structures of costs have not been adapted to recognize these changes and provide a better visition of the processes and calculation of costs for the MANAGEMENT, REGISTRY AND CONTROL OF COSTHE. The intention of this article is to propose a FLEXIBLE STRUCTURE OF COSTS that responds the exigencies OF the MARKET, the COMPANY AND the CLIENT. A structure that allows to pick up the behavior and the costs associated to those processes conducted for diverse modalities.